Building and measuring employee‐based brand equity - King, Ceridwyn and Grace, Debra (European Journal of Marketing, 2010)
Purpose The purpose of this paper is to present the first known empirically‐tested model of Employee Based Brand Equity (EBBE). In doing so, it seeks to provide insight into how organisations can not only effectively manage the internal brand building‐process but also, more importantly, appreciate the subsequent employee effects and organisational benefits. Design/methodology/approach Data were collected via an online survey of 371 employees who work in service organisations, sourced from a market research database list. Findings Strong support was found for nine out of the ten hypothesised relationships, thus providing strong validation for the proposed model. Research limitations/implications The employment of surveys can present data collection problems stemming from such things as lack of willingness to participate on behalf of the respondent, loss of validity when using structured questionnaires, and inherent challenges of wording questions properly. However, in acknowledging these limitations, actions, such as the utilisation of a national database of “opt in” survey participants coupled with the good reliability results and the methodical four‐stage survey design process undertaken, it is suggested that every effort was made to negate the limitations. Practical implications Knowledge is gained from empirically validating a model of EBBE: it further enriches the application of traditional brand management techniques; provides a framework for brand communication training; increases organisational understanding of how to engender positive employee actions; and increases the accountability of such an internal investment by identifying measurable organisational benefits that accrue as a result of such efforts. Originality/value The paper makes three important contributions: expanding the existing brand equity literature to incorporate a third yet equally relevant perspective, that being the employee; the adoption of a multi‐disciplined approach to addressing a marketing issue and, in doing so, extending beyond the connectionist cognitive psychology view of brand equity to incorporate a contextual/organisation cultural element; and reflecting the perceptions of employees, who are currently under‐represented in the internal brand management literature.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC8wMzA5MDU2MTAxMTA0NzQ3Mg